The role of the environment: Silk road in the history of turkic people - Zhumabayeva, Aigerim; Bozhbanbayev, auyrzhan; Turgenbayeva, Aizhan; Aubakir, Arman; Zhanabayev, Kairat (Opción, 2018)
The pathway has been the cause of the development and progress of nations, economic exchange of nations and civilizations throughout history has taken place through roads. Historical and archaeological surveys show that in the past, roads and important ways have been created to connect cities and centers of civilization to the Turkish plateau. The role of the Silk Road as one of the oldest means of communication in cultural communication and tourism development is undeniable. In this paper, attempted to briefly investigate the importance of the Silk Road on the development of its peripheral areas, especially on the Iranian plateau.